Delineation of spring recharge zones using environmental isotopes to support climate-resilient interventions in two mountainous catchments in far-western Nepal - Matheswaran, K.; Khadka, Ambika; Dhaubanjar, Sanita; Bharati, Luna; Kumar, S.; Shrestha, S. (Springer, 2019)
Though springs are the primary source of water for communities in the mid-hills of Nepal, an in-depth scientific understanding of spring systems is missing, preventing the design of effective climate-resilient interventions for long-term sustainability of springs. This study marks the first attempt to combine environmental isotopes analysis with hydrometric and hydrogeological measurements to identify dominant recharge zones for springs in two mountainous catchments—Banlek and Shikarpur—in Far-Western Nepal. In total, 422 water samples collected from rainfall, springs and streams between March 2016 and March 2017 were analyzed for their isotopic composition (d18O and dD). Isotopic composition of rainwater shows seasonality, suggesting that different sources of water vapor cause rains in monsoon and in dry season. Rainfall responses of individual springs were used to identify connections to unconfined and deeper groundwater strata. The isotopic composition of springs in the two catchments ranges from -9.55 to -8.06‰ for d18O and -67.58 to -53.51‰ for dD. The isotopic signature of the spring sources falls close to the local meteoric water line for the corresponding season, indicating strong rainfall contribution to springs. Altitudinal isotopic gradients suggest mean recharge elevation of 2,600–2,700 m asl for springs in Shikarpur, which lies beyond the surface-water catchment, and a recharge elevation of 1,000–1,100 m asl for Banlek, which partially extends beyond the surface-water catchment. The demarcated recharge zones will be used by government agencies to implement recharge interventions to increase the resiliency and reliability of springs in Far-Western Nepal.